AUTHORITY AND LAW ORDER IN THE SPANISH-SPEAKING PAREMIOLOGICAL CONSCIOUSNESS - ELENA Perederi (Ибероамериканские тетради)
The article focuses on the original evaluative Spanish proverbs with the components “rey” and “ley” and is aimed at revealing stereotypes existing in the area of ‘authority’ and ‘law order’, as well as the type of po-litical culture. The analysis of the material has revealed the prevalence of negative appreciation of the power and laws and the lack of cooperation with the people, that is the parochial-subject political culture.